Two worlds colliding: Offenders’ rehabilitation and victims’ protection through mutual recognition of probation measures - Faraldo-Cabana, Patricia (European journal of probation, 2021)
Framework Decision 2008/947/JHA explicitly combines offenders’ rehabilitation with other purposes, such as the improvement of the protection of victims. This article provides one of the first analysis of the aim of ‘victim protection’ in the Framework Decision and of its limited usefulness. The relationship between victims’ right after sentencing and the transfer of probation measures reveals a contradictory system unable to coordinate victims’ protection and compensation and offenders’ social rehabilitation.